Examining User Satisfaction and Continuous Usage Intention of Digital Financial Advisory Platforms in Indonesia: An Integrated Model Approach - Emary, Ibrahiem M. M. El; Sanyour, Rawan; Abdullah, Manal (Journal of Digital Market and Digital Currency, 2025)
This study evaluates user satisfaction (US) and continuous intention (CI) to use digital financial advisory platforms in Indonesia. Utilizing structural equation modeling (SEM) with SmartPLS, we examined the relationships between perceived ease of use (PEU), perceived enjoyment (PE), service quality (SQ), US, and CI. Data were collected from 413 respondents via an online survey conducted between February and March 2024. The descriptive statistics for the main variables indicated that the mean scores ranged from 5.3 to 5.9 on a 7-point Likert scale, with standard deviations between 1.1 and 1.3. Our results show that PEU significantly influences PE (β = 0.923, t-value = 88.677, p < 0.001) and CI (β = 0.471, t-value = 13.950, p < 0.001). PE positively affects the US (β = 0.211, t-value = 7.248, p < 0.001), while SQ is a strong predictor of the US (β = 0.773, t-value = 29.423, p < 0.001). Furthermore, the US significantly impacts CI (β = 0.518, t-value = 15.117, p < 0.001). The R-squared values for the key constructs were 0.851 for PE, 0.876 for US, and 0.878 for CI, indicating substantial explanatory power. These findings underscore the importance of usability, enjoyment, and SQ in enhancing US and retention. The study contributes to the literature by providing an integrated model that combines these key variables, offering a comprehensive framework for understanding user behavior in digital financial advisory platforms. Theoretical contributions include extending the Technology Acceptance Model (TAM) by incorporating enjoyment and SQ. Practical implications suggest that platform providers prioritize user-friendly design, engaging features, and high service standards to improve the US and foster long-term engagement. Future research should explore additional factors, such as perceived security and trust, to further enrich the understanding of user behavior in digital financial services.